IDENTIFIKASI STRUKTUR BAWAH PERMUKAAN MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DI AREA PANASBUMI DESA DIWAK DAN DEREKAN KECAMATAN BERGAS KABUPATEN SEMARANG - Sigit Darmawan; Udi Harmoko; Sugeng Widada (Youngster Physics Journal, 2014)
Diwak and Derekan is one of geothermal manifest which exist in geothermal system of Ungaran. Geoelectric method schlumberger configuration is one of the geophysical methods that used in the exploration of natural resources below the surface. The purpose of researching is to know layer of subsurface structure which control Diwak and Derekan geothermal manifest.Field measurement data in the field are potential differences and currents which can be used to calculate apparent resistivity value. After apparent resistivity value is created then processed using IPI2WIN program to know resistivity value in each layer with geology information validation.The results of the study showed six geoelectric layer of rock that is composed of layers of mudstone, siltstone, tuff, sandstone brecia and pasirtuf with resistivity values and different thicknesses. Interpretation of manually indicate the presence of two down faults that are weak zone where the fluid surface discharge Keyword: Geoelectric, Schlumberger, Geothermal, Fault, Diwak and Derekan